HUKUM DI ERA DIGITAL: PELAKSANAAN E-COURT DAN E-LITIGASI SEBAGAI BENTUK EFISIENSI PADA RUANG LINGKUP PERADILAN PERDATA - Dheya Rahmawati (Jurnal Hukum Lex Generalis, 2024)
The E-Court application is a form of service in the form of E-Government to Citizen, which aims to save time and costs for justice seekers. However, the implementation of E-Court and E-Litigation needs to be understood by the public so that the realization of Efficiency is in line with the goals of simple, fast, and low-cost principles. The research method used is a normative method with a juridical and conceptual approach. The results show that to increase the role of the community in the implementation of the E-Court, the court socializes the implementation of the E-Court in accordance with PERMA No. 7 of 2022. The form of efficiency of the implementation of E-Court and E-Litigation is in the form of simplifying administration, implementing E-Litigation, and a definite and clear trial schedule.